NLP Revolution in Education Feedback Analysis: Trends and Challenges - Maina Changeriwal; Vidhik Sharma; Suhana Arif; Lalit Kumar; Madhur Bharadwaj (International Journal of Wireless Security and Networks, 2023)
Artificial Intelligence (AI) is a rapidly growing area of study in many domains like research and business. Various subsets of AI, such as Machine Learning, Deep Learning, and Natural Language Processing (NLP), are employed to address diverse aspects of data processing and modeling. This review is about the impact of AI on the education system and students feedback for the analysis is required for the enhancement of the technology used in the educational domain. To get this feedback NLP is used to get information about the educational domain. Indeed, understanding domain-specific languages like sarcasm, emoticons, and other forms of nuanced expressions through Natural Language Processing (NLP) has posed significant challenges. These complexities arise due to the non-literal nature of these language elements, making them difficult for traditional NLP techniques to accurately interpret. However, researchers have recognized the importance of capturing these subtleties in educational contexts and have explored various methodologies to overcome these obstacles.
Keywords: Deep Learning; Medical Education; NLP; artificial intelligence; education